Role of Crushed Limestone in Enhancing Growth, Yield and Yield Components of Flax (Linum usitatissimum L.) - azad, neven (Journal of Kerbala for Agricultural Sciences, 2025)
Flax being one of the most important industrial crops in textile after cotton, and for this reason there were a lot of researches conducted around the world. There is a little research about effect of lime on growth and yield of flax. This current experiment was done in Erbil, Kurdistan region - Iraq in the Grdarasha field. Crushed limestone used for detecting its effect on growth and yield of flax at the rates CL0 (control), CL1, CL2, CL3 as (1.5. 3.0 and 4.5 t. ha-1), respectively. Thus, the results showed that when crushed limestone applied at the rate CL1 flax plant achieved the highest Number of branches plant-1, number of capsules plant-1 and number of seeds capsule-1 that were (12.46 branches plant-1, 48.26 capsules plant-1 and 8.36 seeds capsule-1), respectively. On the other hand, the highest values of seed yield, biological yield and harvest index were recorded at the rate of CL3 (238.33, 880.66 and 26.90) kg. ha-1, respectively in comparison to the plots with no crushed limestone application. Limestone can rearrange the soil to maximize crop growth potential. The results suggest probable for further research on the impact of crushed limestone on various crops and comparing it with other types of fertilizers or using it as a supplement to organic and inorganic fertilizers.